2021
DOI: 10.12957/reuerj.2021.61972
|View full text |Cite
|
Sign up to set email alerts
|

Vantagens da ultrassonografia de bexiga na mensuração do volume urinário em pacientes críticos: revisão integrativa [Advantages of bladder ultrasound in measuring urine volume in critically ill patients: an integrative review] [Ventajas de la ecografía vesical en la medición del volumen urinario en pacientes críticos: revisión integradora]

Abstract: Objetivo: identificar as evidências científicas presentes na literatura quanto ao uso da ultrassonografia de bexiga na mensuração do volume urinário em pacientes críticos adultos e idosos em ambiente intra-hospitalar. Método: revisão integrativa baseada nas recomendações PRISMA, realizada em março de 2021, utilizado os descritores “Retenção Urinária”, “Cuidados Críticos”, “Unidade de Terapia Intensiva”, “Ultrassonografia”, “Adulto” e “Idoso”, nas bases Lilacs, PubMed, Scopus, CINAHL, Web of Science. Foi realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…10,11 An integrative review study, which aimed to identify the scientific evidence present in the literature regarding the use of bladder ultrasound, evidenced that 1,928 patients, divided into two groups (group one with bladder ultrasound not available and group two with bladder ultrasound available) and the examination performed by nurses after bladder emptying, obtained as a result that the association of the use of imaging technology reduced the incidence of urinary tract infection (UTI), the time of hospitalization and complications. 12 Another study that aimed to describe the frequency of urinary complaints, the presence of a bladder globe and the real need to perform the VRC after the use of ultrasound, concluded that the use of ultrasound by bedside nurses was more accurate to estimate the volume of diuresis when compared to the volume obtained after the VRC, emphasizing the real accuracy of the use of this technology in the detection of the UR. 13 Although the evidence stems from the relevance of the use of bedside ultrasound in clinical practice and lists the various benefits associated with the use, among them, the reduction of unnecessary bladder catheterization, the decrease in the incidence of UTI related to the use of urinary devices, decreased length of hospital stay, expenses associated with the long period of hospitalization, praxis is still infrequent in the nurse's routine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 An integrative review study, which aimed to identify the scientific evidence present in the literature regarding the use of bladder ultrasound, evidenced that 1,928 patients, divided into two groups (group one with bladder ultrasound not available and group two with bladder ultrasound available) and the examination performed by nurses after bladder emptying, obtained as a result that the association of the use of imaging technology reduced the incidence of urinary tract infection (UTI), the time of hospitalization and complications. 12 Another study that aimed to describe the frequency of urinary complaints, the presence of a bladder globe and the real need to perform the VRC after the use of ultrasound, concluded that the use of ultrasound by bedside nurses was more accurate to estimate the volume of diuresis when compared to the volume obtained after the VRC, emphasizing the real accuracy of the use of this technology in the detection of the UR. 13 Although the evidence stems from the relevance of the use of bedside ultrasound in clinical practice and lists the various benefits associated with the use, among them, the reduction of unnecessary bladder catheterization, the decrease in the incidence of UTI related to the use of urinary devices, decreased length of hospital stay, expenses associated with the long period of hospitalization, praxis is still infrequent in the nurse's routine.…”
Section: Discussionmentioning
confidence: 99%
“…4 The nurse, faced with the diagnosis of UR, must perform the anamnesis and physical examination, however, these methods are influenced by the clinical conditions of the patients, which may lead to loss of precision in the ND. 5 Among the imaging technologies that assist in the verification of urinary volume, ultrasound point-of-care (POCUS) stands out as an effective method for the UR evaluation, as it does not use ionized radiation, it is not invasive, it allows dynamic studies and is performed at the bedside. 6 Ultrasound point-of-care is an excellent tool for the diagnosis of acute UR in the appropriate clinical setting, as it allows the estimation of urinary volume and may determine bladder catheterization, as well as confirmation of the probe balloon inside it.…”
Section: Introductionmentioning
confidence: 99%
“…An integrative review evaluated five studies and listed the main advantages of using US as: effectiveness in measuring urinary volume, reducing the unnecessary use of IUC and the risk of UTI, in addition to early detection of UR ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Una revisión integrativa evaluó cinco estudios y enumeró las principales ventajas del uso de US como: efectividad en la medición del volumen urinario, reducción del uso innecesario de CVP y el riesgo de ITU, además de la detección temprana de RU (11) .…”
Section: Introductionunclassified